Urgensi Literasi Digital di Madrasah Ibitidaiyah: Minority Logic Analyze di Madrasah Ibtidaiyah Nurul Islam - Bali, Muhammad Mushfi El Iq; Rohmah, Desi Ainur (LP. Ma'arif Janggan Magetan, 2023)
Along with the progress of the times, challenges and obstacles continue to develop and change, especially in the field of digital technology. This is caused by changes in human demand and needs from time to time. Therefore, in the era of globalization, digital technology plays a very important role in people’s lives, especially in the world of education. This research aims to contribute to efforts to improve the quality of education, especially in understanding digital literacy. The approach used in this research is qualitative with a case study type. This research took place at Madrasah Ibtidaiyah Nurul Islam, Alaspandan, Pakuniran, Probolinggo. The data collection techniques used in this research were observation, documentation and open interviews. Observations were carried out by directly observing learning activities carried out at Madrasah Ibtidaiyah Nurul Islam. Interviews were conducted with 6 teaching staff who were homeroom teachers in each class. The results of the research show that the synchronization of objectives from various parties, starting from the foundation as the highest administrator of the Madrasah and the head of the Madrasah as the driving force in the running of the wheel of education, as well as parents and students, have a big influence on increasing digital literacy skills at Madrasah Ibtidaiyah Nurul Islam, because of the collaboration able to improve student’s abilities in operating digital literacy. Digital literacy is very important to implement at Madrasah Ibtidaiyah Nurul Islam.